How to run a prison sexually transmitted infection service. Issue 4 (21st March 2011) - Tang, Alan
Abstract : The rationale for providing in-reach services for sexually transmitted infections (STI) and bloodborne viruses (BBV) diagnosis and treatment to prisoners includes the principles underpinning the design and implementation of these services and understanding the special considerations needed to accommodate the effects of the prison regime and categories of prison. Recent literature on service delivery and standards were reviewed. There is ample evidence worldwide that STI and BBV infection are more highly prevalent in prison populations than in the outside community. STI diagnosis and treatment services are therefore an essential component of any STI control programme. Services should be commissioned with characteristics of the prison setting in mind and link in with the local health strategy and action plan. Approval of funding is strongly supported by the quick win from the diagnosis and treatment of highly prevalent STI. The quality of services must be assured by a monitoring and governance framework grounded on national standards.